Using cryoprobes to decrease acquisition times of triple-resonance experiments used for protein resonance assignments. Issue 2 (2003) - Goger Goger, Michael J. Michael J.; McDonnell McDonnell, James M. James M.; Cowburn Cowburn, David David
Abstract : In most structural biology NMR laboratories, instrument time is a limiting factor in the number of structural projects a laboratory is able to support. In the post-genomic era we can expect the number of structural targets to markedly increase. Here we address to what degree recently introduced cryoprobes, which are 3–4 times as sensitive as conventional probes, can alleviate this problem. To evaluate this approach, a set of triple-resonance experiments for protein assignments were acquired with a cryoprobe. We show that, with the cryoprobe, high quality triple-resonance data can be obtained within as 4 hours/experiment. These results show that a full set of data for protein assignments can now be practically collected in 1–2 days.